Serum C-Reactive Protein, Procalcitonin and Lactate Levels as Predictors of Postoperative Surgical Site Infections - ARIJA, DHARMOON; MIRANI, SHAHID HUSSAIN; ABIDEEN, ZAIN-UL-; RASHEED, TAHIRA; HABIBULLAH, HALAR; SAFDAR, RUKKIA (Pakistan Journal of Medical & Health Sciences, 2026)
Background: Surgical site infections (SSIs) continue to be a significant source of morbidity, extended hospital stay and the associated costs after surgery. Predicting the risk of SSI early in the postoperative period is crucial for early intervention and better outcomes. Biomarkers including C-reactive protein (CRP), procalcitonin (PCT), and serum lactate can potentially predict the occurrence of postoperative infection before clinical symptoms manifest. Objective: To assess the predictive ability of serum C-reactive protein (CRP), procalcitonin (PCT) and lactate for postoperative surgical site infections (SSIs) in surgical patients. Methods: The study was a prospective observational study conducted in the Department of Surgery Department of Surgery, Ghulam Muhammad Mahar Medical College Teaching Hospital, Sukkur, a tertiary care teaching hospital from 1st June 2023 to 31st January 2025. We recruited 150 consecutive patients in the postoperative period. CRP, procalcitonin and lactate were measured in the immediate postoperative period. The patients were clinically monitored for the occurrence of SSI according to the diagnostic criteria. Demographic, clinical, and surgical data were also collected. SPSS version 26.0 was used for data analysis, and independent sample t-test and chi-square test were used to compare patients with and without SSI. Results: Thirty nine (26%) patients developed SSI. The mean CRP (91.3±23.6 mg/L), procalcitonin (2.58±0.91 ng/mL) and lactate (3.28±0.76 mmol/L) levels were significantly higher in patients with SSI than those without (p<0.001 for all). SSI was also significantly associated with increased BMI, diabetes mellitus, emergency surgery, and longer operative time. SSI was associated with longer hospital stay and wound complications. Conclusion: Serum C-reactive protein, procalcitonin, and lactate are valuable early predictors of postoperative surgical site infections. Procalcitonin had the highest predictive value. Their use in the postoperative period may assist in early diagnosis and management of SSI.